PENGARUH INTERVENSI KONSUMSI SARI KEDELAI DAN JAHE DENGAN SARI KACANG HIJAU TERHADAP NILAI KOLESTEROL WANITA DENGAN HIPERKOLESTEROLEMIA DI WILAYAH PUSKESMAS NGAWI PURBA - NGAWI - Kurniasih, Erwin (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2021)
High cholesterol can increase the blood vessel disorders through the process of narrowing and blockage of blood vessels called atherosclerosis. Soybeans contain high protein while ginger has phenol compounds as antioxidants. Mung beans have soluble fiber that binds fat in the intestine, which can decrease blood cholesterol levels. The purpose of this research is to determine the effect of soymilk and ginger with mung bean milk on changes blood cholesterol levels in women with hypercholesterolemia in the Ngawi Purba Health Center Working Area. Researcher used Quasi — Experimental with Two Group Pretest — Posttest Control Group. Technique of sampling use Purposive Sampling with total sample is 32 women from 35 women as population with 16 respondents on each group. The results showed that there were differences in blood cholesterol levels before and after therapy in the intervention group (p = 0,000) and the control group (p = 0.022). From the results of the Independent t-test, p value = 0.764. Because the value of p > 0.05, H1 is rejected, that there is no significant difference between soymilk and ginger or mung bean milk on changes in blood cholesterol levels in women with hypercholesterolemia. Based on the results of the research, that content of soybean, ginger, and mung bean are equally effective on decreasing blood cholesterol levels. If seen from the mean difference in blood cholesterol levels before and after soymilk and ginger is only 1.69 mg/dl higher than with mung bean milk. This research recommend not only for who have hypercholesterolemia but peoples to take advantage of soybean, ginger, and mung bean as non – pharmacologic therapy to decrease blood cholesterol levels. Keywords: Blood Cholesterol Levels, Soymilk and Ginger, Mung Bean Milk